BUDAYA DAN PERDAMAIAN : HARMONI DALAM KEARIFAN LOKAL MASYARAKAT JAWA MENGHADAPI PERUBAHAN PASCA GEMPA - Herdiyanto, Yohanes Kartika; Wahyu Yuniarti, Kwartarini (HUMANITAS (Jurnal Psikologi Indonesia), 2012)
The earthquake that took place in Daerah Istimewa Yogyakarta (DIY) and Central Java on 27 May 2006 gave such tremendous impact to individual and socials physical and psychological factor, as well as material damage. Such alterations were potentially threatening harmonious living that has been upheld by the Javanese. Based on the above thought, this research aimed to illustrate the whole psychological overview about the individuals efforts in countenancing the alterations triggered by theearthquake, using the local wisdom which then brought them to harmonious societys life. This study used qualitative method with the ethnography-grounded theoretical approach. One of this researchs essential finding shows that the Javanese still adhering the Javanese local wisdom in countenancing any kinds of post-earthquake alterations. The society was somewhat took any kinds of conflict, such as the unfair disaster-aid distributions and the local residence officers corruption acts, passively. Their passive reaction showed that for Javanese maintaining the socialharmonious life is the most essential life purpose; compared if they had to claim their violated rights.